DIFFERENTIATED GUIDANCE FOR IN-VEHICLE CROWDING LIMITATION IN URBAN BUS SERVICES: Array - Ponkratov, D.; Davidich, N. (Municipal economy of cities (Technical science), 2019)
The level of in-vehicle crowding is one of the main indicators of transit services quality estimation. Excessive crowding causes uncomfortable trip conditions and effect on passengers transport fatigue increasing. In this regard, the in-vehicle crowding level is a normalized value. Along with the fact that the negative impact of excessive in-vehicle crowding on the transit services quality is quite understandable and unmistakable, scientific approaches and methods for determining the rational levels of vehicle occupancy are not justified and require further research. The analysis showed that the existing methods and guidance for in-vehicle crowding limitation do not sufficiently take into consideration the differences in the transit routes, in particular, operational and passenger flow parameters. Instead, both from a scientific and practical point of view, it is more appropriate to use a differentiated approach that will enable individuals to approach the task of choosing the service parameters on each route separately, based on the existing features of its operating. It was supposed that the differentiation of routes in relation in-vehicle crowding limitation problem solution should be based on the passenger flow characteristics, specifically by using of coefficient of unevenness of the passenger flow along the route in the most loaded direction. The hypothesis test was conducted by an experiment on an optimization model, which suppose to minimize total operator and passengers costs. Based on the conducted research, the following rational levels of the bus occupancy are allocated: for the magnitude of the coefficient of unevenness of the passenger flow along the route from 1,0 to 1,2 (very low unevenness), it is necessary to plan the service process with the passenger density on the maximum load section of the route 3 - 4 pass/m2; from 1,2 to 1,4 (low unevenness) - passenger density 4 - 5 pass/m2; from 1,4 to 1,6 (average unevenness) - passenger density 5 - 6 pass/m2; from 1,6 to 1,8 (high unevenness) - passenger density 6 - 7 pass/m2; from 1,8 to 2,0 (very high unevenness) - passenger density 7 - 8 pass/m2; more than 2,0 (exceptionally high unevenness) - passenger density 8 pass/m2. The direction of further research is the development of the proposed approach in terms of adding additional factors and its adaptation for in-vehicle crowding limitation problem solution for other urban transit modes.